Relevansi Pemikiran Ekonomi Yahya Bin Umar Dalam Perspektif Ekonomi Modern - Moh. Subhan (JES (Jurnal Ekonomi Syariah), 2017)
Islam as a religion has rules about life and the life of mankind in plenary, although sometimes it is only globally. The dimension of relationship between humans and god is static, while the dimension of relationship between human and social environment is dynamic and flexible. The second dimension of man is given the broader freedom to make rules and regulations according with the circumstance and condition of times by sticking to the rules of Shari'a. This article will try to elaborate the economic thought of Yahya ibn Umar in his book "Ahkam al-Suq", which is of relevance to the conventional economics. The objective of research is to know whether the brilliant idea of Yahya ibn Umar in his time (Century III H) is still relevant to be applied to the modern era or not. Broadly speaking, Yahya bin Umar’s thought on hisbah and matters related to markets such as; al-ta'sir (pricing), ihtikar (hoarding), and siyasah al-ighraq (dumping). Keywords: al-Ta'sir (pricing), Ihtikar (hoarding), Siyasah al-Ighraq (dumping)